A Case of Glenoid Fossa Fracture, Progressive Ankylosis, Total Joint Reconstruction with Alloplastic Prosthesis to Normalized Function Including Evaluation with F18-PET/CT–a Four Year Follow-up. Issue 1 (February 2017) - Lindell, Björn; Thor, Andreas
Temporomandibular joint replacement (TJR) with alloplastic prosthesis has shown promising long-term results in end stage joint disorders. We present a case of young woman with painful ankylosis that where reconstructed with TJR, due to a complex mandibular fracture with dislocation of the left condyle into the middle cranial fossa two years earlier. At the age of 18 the subject underwent a total joint replacement with custom-made alloplastic TMJ prosthesis. To determine the bone response and remodeling activity around the prosthesis, a F18 PET/CT-scan was used. No sign of increased remodeling or pathology were seen in the imaging after the reconstruction. Four years postoperatively the subject reports no pain and excellent jaw function.